miRNAs and estrogen action - Klinge, Carolyn M. (2012)
MicroRNAs (miRNAs) are short, non-coding RNAs that generally base-pair within the 3′ untranslated region of target mRNAs causing translational inhibition and/or mRNA degradation. Estradiol (E2) and other estrogen receptor (ER) ligands suppress or stimulate miRNA expression in human breast cancer cells, endometrial cells, rat mammary gland, and mouse uterus and post-translationally regulate protein expression. Aberrant miRNA expression is implicated in estrogen-related breast and endometrial cancers and a number of miRNAs downregulate ERα. The role of estrogen-regulated miRNA expression, the target genes of these miRNAs, and the role of miRNAs in health and disease is a “hot” area of research that will yield new insight into molecular mechanisms of estrogen action.